Strategi Pembelajaran Efektif dalam Meningkatkan Kemampuan Baca Tulis Arab Melayu Siswa di MTs - Najwa Muhtadi; Sri Mawaddah (Bayt Al Hikmah: Jurnal Pendidikan dan Pengembangan Masyarakat Islam, 2025)
The teaching of Arabic-Malay literacy at the Madrasah Tsanawiyah (MTs) level plays a strategic role in preserving the Islamic Nusantara literary heritage and in developing students’ linguistic and cultural competencies. This study aims to identify effective instructional strategies to improve Arabic-Malay literacy skills through a literature review of recent scholarly sources. The method used is a library research approach, analyzing journal articles, books, and relevant research reports published between 2017 and 2024. Findings indicate that the success of Arabic-Malay instruction is influenced by teacher competence, the use of contextual learning media, supportive learning environments, and students' linguistic and cultural backgrounds. These results highlight the importance of adopting integrative and adaptive teaching strategies aligned with local contexts and learner characteristics. This study recommends strengthening teacher training, digitizing manuscripts, and providing innovative teaching media as strategic efforts to enhance Arabic-Malay literacy education in MTs.